Knowledge transfer: an information theory perspective. Issue 3 (1st August 2017) - Sudhindra, S.; Ganesh, L. S.; Arshinder, K.
Abstract: Personalization and codification are two dominant knowledge transfer (KT) mechanisms found in organizations and organizational networks. This paper proposes a theoretical model of KT that explains organizations' choice of KT mechanisms in terms of the tacitness of knowledge being shared and the corresponding information content. Shannon's entropy, an information theoretical concept, has been used to define the constructs of tacitness and information content and explain their influence on the choice of the corresponding KT mechanisms. Contributions of the paper include (a) use of information content as a predictor of the choice of KT mechanisms, (b) development of an expression for tacitness, and an intuitive explanation of the tacit-explicit continuum, (c) characterization of product variety in terms of information content, and (d) development of a KT theoretical model that can be operationalized for predicting the choice of KT mechanisms in real-life situations.